Pra-pendampingan penggunaan digital tools dan kecerdasan buatan dalam penulisan buku berjenjang terkait perubahan iklim - Silvhiany, Sary; Inderawati, Rita; Raharjo, Makmum; Anggraini, Hesti Wahyuni; Dari, Tita Ratna Wulan (STAI Auliaurrasyidin Tembilahan, 2025)
Teacher groups in Musi Banyuasin district have great potential in developing learning materials, in the form of leveled books. Their significant benefits in meeting students' reading needs according to their level of difficulty and understanding make leveled books an important product that can be created by classroom teachers. This book also has the potential to be a medium to increase students' awareness of global issues, including climate change, through the integration of relevant content in learning. For this reason, the service team from FKIP Sriwijaya University designed a program to facilitate the assistance and training activities needed. As the first step of the program, the service team conducted an initial exploration regarding the teacher participants' mastery of digital tools and artificial intelligence (AI). The method of the exploration activity was to distribute questionnaires that must be filled in by the participants. The result is that 59.1% of teachers understand the concept of leveled books and 63.6% of teachers use leveled books in the classroom. Unfortunately, 63.6% of teachers stated that they had never made leveled books for their class. Regarding the role of digital tools, teachers seem to be familiar with Canva and AI. The data shows that 81.8% of teachers often use Canva to create teaching materials. There are also other tools that are utilized, such as YouTube, ChatGPT, and YouTube. It can be concluded that, the process of mentoring and training for making tiered books is mandatory considering that teachers already have basic knowledge related to digital tools and AI.